Au/Ni Coaxial Nanopillar Microarray Electrodes for Red Blood Cell Concentration Detection - Chung, Po-Min; Lin, Ying-Ting; Wang, Gou-Jen (IEEE sensors journal, 2023)
In this study, an Au/Ni nanopillar microarray electrode for red blood cell concentration detection was proposed. Electrodes were fabricated using anodic aluminum oxide (AAO) as the template, followed by photolithography, electroforming, gold immersion to form an Au/Ni coaxial nanopillar array electrode. The diameter of the Au/Ni nanopillar microarray electrode was 50-μm. The average size of the coaxial nanopillar was measured to be approximately 140 nm, indicating that the thickness of the gold shell was approximately 25 nm. The weight and atomic percentage ratio of Au/Ni were measured to be 84.94/19.06 and 55.87/44.13. The Stochastic collision nanoelectrochemistry of insulating particles, along with chronoamperometry, was implemented to measure cell concentration. The characteristics of the fabricated electrode were first verified by the cell concentration detection of KU812. The subsequent whole blood sample detection verified that the proposed sensing scheme has two linear detection ranges, 4 × 10 7 - 2 × 10 9 and 2 × 10 9 -4.88 × 10 9 cells/mL, with R 2 of 0.999 and 0.999, respectively. The detection recovery rates of the two blood samples were measured to be 102.4% and 109.8%, respectively. The experimental results confirmed that the fabricated electrodes are feasible for detecting red blood cell concentrations in real blood samples.